Chaplin, the collection - Chaplin, Charles (Madacy Music Group [distribución])
Este volumen incluye los cortometrajes: Charlot garçon de theâtre (1920), The musical tramp (Keystone, 1914), Charlot et Mabel aux courss (1914), Recreation (Keystone, 1914).